Memory making in a pandemic. Spaces and bodies simulations in commemoration practices during lockdown - Mazzucchelli, Francesco; Panico, Mario (E|C, 2021)
This paper seeks to provide an investigation of the use of memory spaces and the practice of commemoration during the first wave of the Covid-19 pandemic, when people were forced to stay at home due to the lockdown. In particular, the authors point out how the reconfiguration of urban and domestic spaces, together with the increasing use of electronic and technological devices, has contributed to the production of new forms of memorial gathering, in which the collective subject has taken on different semiotic configurations each time. All the case studies in this article are related to a specific memorial day: the Italian commemoration of the 25th April, the date of Nazi-fascist liberation in 1945.